AKUNTANSI, TRANSPARANSI DAN AKUNTABILITAS KEUANGAN PUBLIK - Setiyanti, Sri Wiranti (JURNAL STIE SEMARANG, 2011)
Local   government   financial    reports   that   are   generated    through   the  process    of accounting  is a form  of transparency  and accountability   in public financial  management.   To be able to produce financial  statements  that the better  (the challenge)  required  skilled  accounting personnel  in local governments.   this can be done through  the activities  of technical  accounting guidance for  local government  employees  who are assigned  as a financial   manager  or through the recruitment  of new employees  who have the ability  of local financial   accounting. In  addition  to skilled  accounting  personnel,   it also  needed  a system  and procedures adequate bookkeeping  and accounting policies  to guide staff in managing  local financial.